THERMODYNAMIC STUDY OF TENSION IN THE WORKPLACE WITH HIGH HEAT - , А. С., С. Ю., Г. Г., В. М. (Municipal economy of cities (Technical science), 2013)
The issues of improving existing methods for studying the thermodynamic tension in the workplace, improving the accuracy of measurements of thermal radiation, and hence the reliability of the data.